The management century : a critical review of 20th century thought and practice - Crainer, Stuart (The Jossey-Bass business & management series, 2000)
"Crainer shows us that a careful study of the history of management holds vital clues to its future. There are lessons to be learned from early giants such as Henri Fayol, originator of the fourteen general principles of management, and from more contemporary figures such as W. Edwards Deming, the American whose concept of Total Quality Management revolutionized the Japanese auto industry. Decade after decade, Crainer points out, each new trend in management thinking has been shaped by the successes - and shortcomings - of the concepts that preceded it."--Jacket